2001
DOI: 10.1345/aph.10315
|View full text |Cite
|
Sign up to set email alerts
|

Statin—Fibrate Combination Therapy

Abstract: Combination therapy with a statin and fibrate offers significant therapeutic advantage for the treatment of severe or refractory mixed hyperlipidemia. Although such a combination does increase the risk of myopathy, with an incidence of approximately 0.12%, this small risk of myopathy rarely outweighs the established morbidity and mortality benefits of achieving lipid goals. Nevertheless, a higher incidence of myopathy has been reported with statin monotherapy. When monotherapy with a statin fails to control mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
3
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(137 citation statements)
references
References 85 publications
(93 reference statements)
3
125
3
6
Order By: Relevance
“…Desde a época em que o clofibrato era o único medicamento disponível desse grupo, sabe-se que os fibratos aumentam o conteúdo de colesterol da bile, levando à maior litogenicidade. 8 Tem sido verificado na prática, que a associação das estatinas com os fibratos, aumenta a chance de hepatotoxicidade para 3,2%. 9 …”
Section: Hepatotoxicidade Com Fibratosunclassified
“…Desde a época em que o clofibrato era o único medicamento disponível desse grupo, sabe-se que os fibratos aumentam o conteúdo de colesterol da bile, levando à maior litogenicidade. 8 Tem sido verificado na prática, que a associação das estatinas com os fibratos, aumenta a chance de hepatotoxicidade para 3,2%. 9 …”
Section: Hepatotoxicidade Com Fibratosunclassified
“…Synergistic Effect of Fibrates and Statins on the Induction of PDK4 mRNA Since it is known that the risk of rhabdomyolysis increases with combination therapy using fibrate and statin, 5,6) we next examined the effect of bezafibrate together with a statin, pravastatin or simvastatin, on the expression of PDK4 mRNA in the liver and muscles of mice. A higher dose of bezafibrate (2%) gave a result similar to that with a lower dose (0.3%) on the expression levels of PDK4 Table 1) of the drug indicated for 24 h. The drugs used were; Pra, pravastatin; Sim, simvastatin; Ofl, ofloxacin; Bez, bezafibrate from Bezatol; Nor, norfloxacin; Lev, levofloxacin; bez, bezafibrate of reagent grade.…”
Section: Inefficient Induction Of Pdk4 Mrna By Statins and New Quinolmentioning
confidence: 99%
“…Though synergistic clinical benefits of combination therapy with fibrates and statins have been reported, [1][2][3][4] the problem of these drugs especially in combination therapy is the risk of rhabdomyolysis. 5,6) The biochemical basis for the primary fibrate and/or statin-induced rhabdomyosysis is not well understood. 7,8) We previously reported that fibrates rapidly induce pyruvate dehydrogenase kinase 4 (PDK4) mRNA in various tissues of mice.…”
mentioning
confidence: 99%
“…However, concomitant use of a fibrate and a statin has been associated with an increased risk of myopathy. It appears that this risk may differ depending on which statin and fibrate are administered [24,25]. In the present study, we used the combination of bezafibrate (200 mg/day) and rosuvastatin (2.5 mg/day), and showed that administration of the two drugs at these dosages was both effective and safe.…”
Section: Discussionmentioning
confidence: 69%